2019
DOI: 10.1016/j.envint.2019.104963
|View full text |Cite
|
Sign up to set email alerts
|

Neurological symptoms associated with oil spill response exposures: Results from the Deepwater Horizon Oil Spill Coast Guard Cohort Study

Abstract: Introduction: The Deepwater Horizon (DWH) oil spill was the largest marine oil spill in U.S. history, involving the response of tens of thousands clean-up workers. Over 8500 United States Coast Guard personnel were deployed in response to the spill. Little is understood about the acute neurological effects of oil spill clean-up-related exposures. Given the large number of people involved in large oil spill clean-ups, study of these effects is warranted. Methods: We util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 22 publications
(36 reference statements)
1
13
0
1
Order By: Relevance
“…Similar to the sex-specific findings from our study, a recent study on the acute neurological effects of oil-spill cleanup-related exposures based on the Deepwater Horizon Oil Spill Coast Guard Cohort also reported sex-related neurological symptoms that were stronger in males than females [ 48 ] . We speculate that the sex difference in response to oil spill chemicals may be largely immune mediated as sex-specific differences in the immune response are well documented in the literature [ 49 ] .…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the sex-specific findings from our study, a recent study on the acute neurological effects of oil-spill cleanup-related exposures based on the Deepwater Horizon Oil Spill Coast Guard Cohort also reported sex-related neurological symptoms that were stronger in males than females [ 48 ] . We speculate that the sex difference in response to oil spill chemicals may be largely immune mediated as sex-specific differences in the immune response are well documented in the literature [ 49 ] .…”
Section: Discussionsupporting
confidence: 89%
“…The DWH-CG Study evaluated acute neurological and mental health symptoms among Coast Guard responders during their response to the DWH oil spill. Increased prevalence of headaches, lightheadedness, difficulty concentrating, numbness/tingling sensation, blurred vision, and memory loss/confusion was associated with elevated frequency of crude oil exposure via inhalation and via skin contact (Krishnamurthy et al 2019;Rusiecki et al 2018). Exposure to both crude oil and oil dispersants yielded associations appreciably greater in magnitude than for crude oil alone (Krishnamurthy et al 2019).…”
Section: Humansmentioning
confidence: 94%
“…Increased prevalence of headaches, lightheadedness, difficulty concentrating, numbness/tingling sensation, blurred vision, and memory loss/confusion was associated with elevated frequency of crude oil exposure via inhalation and via skin contact (Krishnamurthy et al 2019;Rusiecki et al 2018). Exposure to both crude oil and oil dispersants yielded associations appreciably greater in magnitude than for crude oil alone (Krishnamurthy et al 2019). Wang et al (2020) found elevated prevalence of anxiety and depression among responders reporting longer oil spill response work duration and intensity, increasing exposure to crude oil, and physical symptoms.…”
Section: Humansmentioning
confidence: 99%
“…The USCG study reported positive associations between exposure to crude oil, and in some cases oil and dispersant mixtures, and acute respiratory symptoms (Alexander et al, 2018); neurological symptoms including headache, lightheadedness, difficulty concentrating, numbness/ tingling sensa-tion, blurred vision, and memory loss/ confusion (Krishnamurthy et al, 2019); heat stress (Erickson et al, 2018); and skin issues, as well as some gastrointestinal and genitourinary symptoms that have not previously been well evaluated (Rusiecki et al, 2018).…”
Section: Worker Health Findingsmentioning
confidence: 99%
“…Findings by McGowan et al (2017) suggest associations between exposure to dispersants, specifically Corexit EC9527A or Corexit EC9500A, and acute adverse health effects (e.g., respiratory and eye irritation and chest tightness at the time of the oil spill work as well as symptoms that were pres-ent at the time of study enrollment one to three years after the spill). Although only 5% of the Coast Guard personnel who responded to the Deepwater Horizon Oil Spill Cohort study health questionnaire reported contact with both oil and dispersants, for example, through assignments to conduct Special Monitoring of Applied Oil Spill Technologies (Levine et al, 2011), self-reported adverse neurological health effects were worse for those workers than for those exposed only to oil, and heat exposure also exacerbated symptoms (Krishnamurthy et al, 2019). However, these authors cautioned that self-reported information can be subject to bias, and they did not have information about who was where and when in reference to possible exposures.…”
Section: Dispersantsmentioning
confidence: 99%